MARE’S MILK: THERAPEUTIC AND DIETARY PROPERTIES (Review article) - B. Bimbetov; A. Zhangabylov; S. Aitbaeva; V. Benberin; H. Zollmann; A. Musaev; M. Rakhimzhanova; G. Esnazarova; A. Bakytzhanuly; N. Malaeva (Scientific Journal of Pedagogy and Economics, 2019)
The review article is devoted to therapeutic and dietary properties of mare's milk. Literature review is carried out, historical facts of application of this product at various diseases and conditions are resulted, qualitative composition of milk and the research conducted by foreign and domestic authors about application of mare's milk medical-dietical product are described. Large-scale production of sublimated pasteurized mare's milk in Kazakhstan will give a new impetus to the expansion of clinical trials in various aspects and the use of this product with a long shelf life.